Dynamic mixed-mode fracture in SCC reinforced with steel fibers: an experimental study. (July 2019) - Ruiz, G.; de la Rosa, A.; Almeida, L.C.; Poveda, E.; Zhang, X.X.; Tarifa, M.; Wu, Z.M.; Yu, R.C.
Abstract : Highlights: First experimental study on dynamic mixed-mode fracture of fiber-reinforced concrete. Experimental demonstration that the crack propagation may be stable or unstable depending on loading rate and fiber content. Fracture is mainly transgranular, but maybe inter- or trans-granular at stable cracking. Higher dynamic increase factor for peak loads for higher loading rate and fiber content. Significant higher DIF for peak loads in mixed-mode that in mode I. Abstract: The objective of this work is to study the influence of fiber content and loading rate on the dynamic mixed-mode fracture of self-compacting concrete. Three amount of steel fibers, 0%, 0.2%, 0.4% and 0.6% in volume ratio, were added to cast prismatic beams. Each beam was sawn at one quarter span to produce a half-depth notch. Three-point bending tests were performed at four loading rates: two (2.2 µm/s and 2.2 mm/s) with a servo-hydraulic machine; the other two (1.77 m/s and 2.66 m/s) through a drop-weight impact device. The latter ones were also recorded with a high-speed video camera to follow the crack propagation process. Results show that both the peak load and the crack inclination angle increase for faster loading rates. In addition, highly reinforced beams exhibit profuse crack branching. As the fiber ratio increases, it is also observed that the main crack may either bifurcate or abruptly change its path when it gets closer to the loading point. Numerical simulations based on an eigensoftening approach in a meshfree framework were also carried out to reproduce the observed phenomena.